Diphteri outbreak investigation in restricted islamic boarding school Boyolali district, Central Java province, Indonesia 2018 - Rido Illahi Ayef Eka Putra; Teguh Tri Kuncoro; Dibyo Pramono (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Background: On May 13, 2018 at 10.08 a.m, Boyolali District Surveillance Officer (DSO) was informed by the Head of the Boyolali Health Office Disease Control Division via the WhatsApp group (WA), that there was found one diphtheria-suspected patient from El-Abror Islamic Boarding School in Candi, Ampel sub-district. Suspected patien was referred from Sumber Waras Health Clinic to Pandan Arang Public Hospital (RSUPA) in Boyolali district, Central Java province to be isolated in an isolation room. Investigation aims to explore the information regarding the spread of risk factors of diphtheria in the El-Abror Islamic boarding school. Methods: Data were collected through interviews and field observations to all male students, female students, teachers and residents living in the El-Abror Islamic boarding school 147 in total. The criteria for the cases used are those diagnosed with fever of more than 37C who live in the El-Abror boarding school from April 10, 2018 to May 24, 2018. Results: The index case in this diphtheria outbreak was 2 female students who were diagnosed with symptoms of fever, tonsillitis, pseudomembrane who treated at the Pandan Arang Hospital (RSPA) in Boyolali district. during the investigation had found 20 diphtheria-suspect in total. Attack rate (AR) based on sex,female group (55%) was higher in comparing to male group (31.03%). Attack rate (AR) based on age, most suspects were found in the 11-15 year age group (63.15%). There were no cases of death in this diphtheria outbreak (CFR = 0%). Risk factors for transmission are immunization status and lighting conditions and ventilation that did not meet the healthy home criteria. Conclusions: ORI (Outbreak Response Immunization) has done as intervention for tackling this outbreak. Sustainability of surveilance system should be developed for primary health worker to monitor and evaluate immunization program. DSO (District Surveilance Officer) should engange community to develop immunization program by increasing health promotion in Islamic Boarding School.